2003
DOI: 10.1097/01.shk.0000092697.10326.8b
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Pyruvate Provides Durable Protection Against Inflammation-Induced Intestinal Epithelial Barrier Dysfunction

Abstract: Ethyl pyruvate (EP) has been shown to be an effective anti-inflammatory agent. Herein, we sought to test the following hypotheses: 1) the pharmacological effects of EP persist after cells have been exposed to the compound in vitro, even if the cultures are washed to minimize the amount of EP that is retained in the media; 2) the pharmacological effects of EP persist in vivo, even after waiting a prolonged period (i.e., 6 h) after the last dose of the compound; and 3) the in vivo pharmacological effects of EP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 42 publications
1
42
1
1
Order By: Relevance
“…Thus, the activity of ethyl pyruvate as an ROS scavenger might account for its antiinflammatory properties, since other ROS scavengers, such as N-acetylcysteine, are known to inhibit expression proinflammatory genes, at least under some conditions (Song et al, 2004). This notion, however, is not supported by observations recently reported by Sappington et al (2003a), who showed that transient exposure to ethyl pyruvate inhibits iNOS expression in immunostimulated Caco-2 human enterocyte-like cells, even when the compound is removed from the culture medium by thorough washing of the cells. In contrast to the ROS-scavenging hypothesis, which seems incompatible with the data obtained by Sappington et al (2003a), covalent modification of the p65 subunit of NF-B, as suggested by the findings reported herein, is entirely compatible with the observation that transient incubation with ethyl pyruvate provides a durable anti-inflammatory effect even in the absence of ongoing exposure to the compound.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, the activity of ethyl pyruvate as an ROS scavenger might account for its antiinflammatory properties, since other ROS scavengers, such as N-acetylcysteine, are known to inhibit expression proinflammatory genes, at least under some conditions (Song et al, 2004). This notion, however, is not supported by observations recently reported by Sappington et al (2003a), who showed that transient exposure to ethyl pyruvate inhibits iNOS expression in immunostimulated Caco-2 human enterocyte-like cells, even when the compound is removed from the culture medium by thorough washing of the cells. In contrast to the ROS-scavenging hypothesis, which seems incompatible with the data obtained by Sappington et al (2003a), covalent modification of the p65 subunit of NF-B, as suggested by the findings reported herein, is entirely compatible with the observation that transient incubation with ethyl pyruvate provides a durable anti-inflammatory effect even in the absence of ongoing exposure to the compound.…”
Section: Discussioncontrasting
confidence: 54%
“…EP is a pharmacological inhibitor of HMGB1 secretion (13,14,18,31,41,53,59,62,73,74,82); however, the precise mechanism(s) that mediate its inhibitory effects have not been identified as of yet. Treatment with EP has been shown to improve survival and alleviate organ dysfunction in a wide variety of preclinical models of critical illness (19,20) including the amelioration of IRI in organs (13,34,77,84) including the kidney (13).…”
Section: Discussionmentioning
confidence: 99%
“…The well-described differences in the pharmacological effects of EtP and NaP [10][11][12][13][14][15][16] may reflect the greater lipophilicity of EtP. 16) Our data presented in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Despite its greater stability, EtP also appeared to be more effective than sodium pyruvate (NaP) under various stress conditions. [10][11][12][13][14][15][16] An in vivo model of LPS-induced hepatocellular injury indicated both EtP and NaP to have protective properties, although EtP was more efficacious.…”
mentioning
confidence: 99%